Studying Radiation and Reaction Effects on Unsteady MHD Non-Newtonian (Walter’s B) Fluid in Porous Medium - Gamal M. Abdel-Rahman Rashed; Faiza M. N. El-fayez (Abstract and Applied Analysis)
This paper describes the studied effects of thermal radiation and chemical reaction on unsteady MHD non-Newtonian (obeying Walter’s B model) fluid in porous medium. The resulting problems are solved numerically. Graphical results for various interesting parameters are presented. Also the effects of the different parameters on the skin-friction and the heat fluxes are obtained and discussed numerically.